Henry Kissinger : perceptions of international politics - Starr, Harvey (University Press of Kentucky, 1984)
Henry Kissinger conducted American foreign policy with a distinctive assurance and panache that gave dramatic force to his tenure as secretary of state. His was the shaping hand in decisions that led to detente with the Soviet Union, to opening relations with the People's Republic of China, and to ""shuttle"" diplomacy in the Middle East and the disengagement of Egypt and Israel during the 1973 war. Taking a fresh look at the statecraft of Henry Kissinger, Harvey Starr brings to bear a variety of analytical methods on data drawn from different stages in Kissinger's career to define and explain.